2011
DOI: 10.1007/s10734-011-9406-2
|View full text |Cite
|
Sign up to set email alerts
|

Student mobility reviewed: attraction and satisfaction of international students in Turkey

Abstract: Building on international migration theories and the literature on the dynamics of student mobility, this study sketches a two-dimensional framework and examines its utility to understand the rationales of in-bounding student mobility in Turkey. The empirical part of the study was conducted with 331 international students studying in public universities of Turkey. The results suggest that private rationales are prominent for students coming from Western and economically developed countries. In contrast, econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
0
20

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(133 citation statements)
references
References 32 publications
9
104
0
20
Order By: Relevance
“…The internationalization of higher education has recently been on the agenda of both international (De Wit, 2002;Altbach, 2007, Knight, 2015 and national (Kondakçı, 2011;Erdoğan, 2014aErdoğan, ,2014bErgin, 2015) researchers. Although it does not have a definition agreed by all the researchers, it can be defined as "internationalization at the national/sector/institutional levels is the process of integrating an international, intercultural or global dimension into the purpose, functions or delivery of higher education at the institutional and national levels" (Knight, 2008, p. 21).…”
Section: Discussionmentioning
confidence: 99%
“…The internationalization of higher education has recently been on the agenda of both international (De Wit, 2002;Altbach, 2007, Knight, 2015 and national (Kondakçı, 2011;Erdoğan, 2014aErdoğan, ,2014bErgin, 2015) researchers. Although it does not have a definition agreed by all the researchers, it can be defined as "internationalization at the national/sector/institutional levels is the process of integrating an international, intercultural or global dimension into the purpose, functions or delivery of higher education at the institutional and national levels" (Knight, 2008, p. 21).…”
Section: Discussionmentioning
confidence: 99%
“…This widely cited framework has proven useful in explaining global mobility, particularly to the most resourced countries in the West, but does not fully capture the emerging growth of regional mobility taking place in other parts of the world. With such broadening of international destinations, many have worked to draw attention to the role of less-studied countries or regions (e.g., Kondakci 2011;LeeandKim 2010;Liand Bray 2007;McMahon 1992;Sehoole 2011). …”
Section: Sadc 75%mentioning
confidence: 99%
“…There has also been an emerging and significant body of research that differentiates educational migration from the perspective of non-Western and economically developing countries (Cantwell et al 2009;Kondakci 2011). Previous research has also shown that the motivations for and experiences of those migrating to nearby versus distant countries reportedly differ.…”
Section: Sadc 75%mentioning
confidence: 99%
See 1 more Smart Citation
“…Kondakci (2011) argued that the satisfaction of international students with universities abroad is affected by different factors related to the country of origin. In this study, the majority of participants were young, with little experience, having lived in non-democratic countries, and raised and educated in a different value system.…”
Section: Level Of Satisfaction Of International Business Studentsmentioning
confidence: 99%